Penerapan Model Pembelajaran Problem Based Learning Melalui Media Digital Dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Man 1 Pringsewu - Azzahra Melani; Yunisca Nurmalisa; Nurhayati . (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model through digital media on students’ critical thinking skills at MAN 1 Pringsewu. The research employed a quasi-experimental method using a pretest–posttest control group design. The experimental class implemented PBL using Padlet, while the control class used PBL through Google Classroom. Data were analyzed using an Independent Sample t-test and N-Gain Score with SPSS 26. The results indicated a significant difference between the two classes (Sig. 0.000 < 0.05). The average N-Gain score of the experimental class was 76.16 (effective), higher than the control class at 57.08 (moderately effective). These findings demonstrate that Padlet-based PBL is more effective in improving students’ critical thinking skills